The effect of warm compress therapy on labor pain during the active phase of the first stage of labor: A pre-experimental study - Aini, Apriyanti; Lamdayani, Rinda; Apriyanto, Apriyanto (School of Health Sciences Al-Ma'arif, 2026)
Background: Labor pain during the active phase of the first stage of labor is a significant physiological and psychological challenge for women and may influence labor progression and childbirth experience. Non-pharmacological interventions are increasingly recommended to support maternal comfort and promote physiological labor. Warm compress therapy has been widely applied during the second stage of labor; however, evidence regarding its effectiveness during the active phase of the first stage of labor remains limited. Objective: This study aimed to examine the effect of warm compress therapy on labor pain during the active phase of the first stage of labor. Methods: This study employed a quantitative approach using a pre-experimental one-group pretest–posttest design. The study was conducted at PMB Erni Artiqoh, Bumi Makmur Village, involving 20 laboring women selected through total sampling. Labor pain intensity was measured using a numerical rating scale before and after the application of warm compress therapy. The intervention consisted of warm compress application at a temperature of 38–45°C for approximately 20 minutes during the active phase of labor. Data were analyzed using univariate analysis and the Wilcoxon signed-rank test. Results: The results showed a clear reduction in labor pain intensity following the intervention. Before the intervention, most participants reported severe pain levels, while after warm compress therapy, pain scores shifted to mild-to-moderate levels. The Wilcoxon signed-rank test demonstrated a statistically significant difference in labor pain intensity before and after the intervention (p = 0.001), indicating that warm compress therapy effectively reduced labor pain during the active phase of the first stage of labor. Conclusion: Warm compress therapy was found to be effective in reducing labor pain during the active phase of the first stage of labor. This non-invasive, low-cost intervention can be safely integrated into routine midwifery care to enhance maternal comfort during childbirth.